Optimasi Suhu dan Lama Pemanasan dalam Pembentukan Kompleks Inklusi Glibenklamid-β-Siklodekstrin dengan Metode Sealed-Heating (Optimization Temperature and Heating Time Formation of Inclusion Complexes Glibenclamide-β-Cyclodextrin by Sealed-Heating Metho - Aslyni Putri Suranina Barus; Lidya Ameliana; Dwi Nurahmanto (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Glibenclamide is a second-generation sulfonylurea that used for type II diabetes mellitus. Glibenclamide is included in the biopharmaceutical classification system (BCS) class II, which has a low solubility and high permeability. One effort that can be done to improve the solubility of drug is inclusion complexation. The aims of the study was to determine temperature and heating time on inclusion complexation of glibenclamide-β-cyclodextrin using sealed-heating method. Optimization done using a factorial design for two factors with 22 number of experiments. Inclusion complexes were determined its miosture content, solubility and in vitro dissolution. Moisture content study showed that F1> FB > FA > FAB. The results of solubility study were analyzed statistically using One-Way ANOVA and least significantly different (LSD). Statistical analysis showed that each formula had a significant difference solubility with FAB > FB > FA > F1>Control. Optimization on in vitro dissolution showed that FAB was an optimum formula with drug release of 87.24% within 180 min. This formula was characterized by DSC to observed for broadening, shifting and appearance of new peaks or disappearance of certain peaks. DSC analysis was indicated that inclusion complexation between glibenclamide and β-cyclodextrin was formed. Keywords: glibenclamide, β-cyclodextrin, inclusion complexe, sealed-heating